Methodology of experience action in spatial restriction: Didactics of the m2. Located study - Pino Madariaga, Jenny; Rivera Larraín, Ismael (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Framed in the Teaching area and specifically referring to new teaching formulas, this reflection delves into the Didactic methodology of m2 (IP 269.529), which proposes its own theoretical framework and references and which is presented as a contribution to the training of trainers, as well as a possibility of education in the classroom. Opportunities for expression and creation in spaces of restriction, resignifying the school, the playgrounds and the classrooms themselves, promoting meaningful experiences of knowledge and solutions. Relieving artistic processes of experience - action in education, as well as the application of new methodologies possible to transfer.